Breaking the Hourglass: Partnerships in Remote Management Settings, The Cases of Syria and Iraqi Kurdistan (Tufts Archival Research Center, 2018)
Breaking the Hourglass: Partnerships in Remote Management Settings, The Cases of Syria and Iraqi Kurdistan. Briefing Paper 1, by Kimberly Howe, Elizabeth Stites, and Danya Chudacoff